Limited periauricular facelift how to deal with short scar: a technical contribution: Lifting facial periauricular limitado: cómo tratar una cicatriz corta: una contribución técnica - Centurion Rivas, Patricio (2022)
Facelift, currently, is one of the most demanded aesthetic procedures and considered as the Ultimate Facial Rejuvenation Surgery. The purpose of this present technique is to offer an alternative surgical procedure of reduced scars, limited to the peri-auricular area, easily reproducible, without the need of extended incisions far beyond the retro-auricular sulcus neither the need of flaps for the temporal region. Our technique is based on a block reposition of the pre auricular area, cervical flaps movilization and rotation of a retro auricular flap, avoiding flaps and incisions in the temporal and occipital region; therefore, minimizing visible scars (occipital pre-pilose scar), wide-tissue undermining, and in addition reducing the risk of damaging nerve structures with less recovery time for our patients, achieving natural and long lasting results.